Hexagonal pentlandite, preparation method thereof and electrocatalytic hydrogen evolution
By transforming cubic nickel -yellow iron ore under high -pressure and high temperature conditions into hexagonal nickel -yellow iron ore, the problem of insufficient hydrogen analysis of existing nickel -yellow iron ore has been solved, and more efficient electrocatalyst hydrogen analysis performance has been achieved.
Patent Information
- Application Number
- CN202311417403.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-10-27
AI Technical Summary
The existing cubic crystalline nickel pyrite still needs to be improved in electrocatalytic hydrogen evolution performance, and its synthesis procedure is complex and uneconomical.
By concentrating the hemiculous nickel -yellow iron ore of the cubic nickel mines at 1 to 2GPa and 500-700 ° C, it is used as a hydrogen analyzed catalyst.
The hexagonal nickel -yellow iron ore showed a potential of not less than 60mV under acidic conditions, and there was no active loss at 50h at high current density. The hydrogen analysis performance was significantly higher than the cubic nickel mines and known nano sulfide catalysts.
Smart Images

Figure CN117385471B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to hexagonal pentlandite, a preparation method thereof and electrocatalytic hydrogen evolution. Background Art
[0002] Each kilogram of hydrogen can release 140 million joules of heat when burned, while the heat released by automobile fuel is only 46 million joules / kilogram. Therefore, the development and utilization of hydrogen energy is an important way to reduce dependence on oil and achieve carbon neutrality. Electrolysis of water to produce hydrogen (hydrogen evolution reaction) is an effective method for industrial production of hydrogen. Platinum and its alloys play a dominant role in the hydrogen evolution reaction (HER) and allow the production of H2 in acidic electrolytes with low overpotential, fast reaction rate and high current density (Huang et al. 2018; Shi et al. 2021). However, low natural abundance and high price hinder the sustainability of platinum hydrogen production. Non-precious metal HER catalysts, such as ultrathin metal Fe-Ni sulfide nanosheets, show high HER activity (Long et al. 2015). Although this material is very effective, the requirement for specific surface shapes and complex synthesis procedures make these materials uneconomical. The natural ore pentlandite (M9S8, M = Fe, Ni, Co in different proportions) was used as a direct “rock” electrocatalyst without further surface modification for HER. Under acidic conditions and high current density, it can reach 10 mA cm -2 The overpotential of cPn is 280 mV and there is no activity loss for about 170 h (Konkena et al. 2016). However, the hydrogen evolution performance of the existing cubic pentlandite (cPn) still needs to be improved. Summary of the invention
[0003] In view of this, the technical problem to be solved by the present invention is to provide a hexagonal pentlandite, a preparation method thereof and electrocatalytic hydrogen evolution. The hexagonal pentlandite provided by the present invention can be used as a hydrogen evolution catalyst and has better hydrogen evolution performance.
[0004] The present invention provides a hexagonal pentlandite, characterized in that the space group of the hexagonal pentlandite is P63 / mmc;
[0005] The unit cell parameters include: α = 90°, β = 90°, γ = 120°;
[0006] Preferably, the phase boundaries of the hexagonal pentlandite and cubic pentlandite are 1 GPa / 550°C, 2.1 GPa / 450°C, 4 GPa / 258°C and 6.2 GPa / 200°C, respectively;
[0007] The phase boundary curve conforms to formula (1);
[0008] T=660e -2.203P (1);
[0009] In formula (1), e is a natural constant, the unit of T is °C, and the unit of P is GPa.
[0010] Preferably, in the hexagonal pentlandite, the ratio of the number of metal atoms to the number of sulfur atoms is 9:8.
[0011] Preferably, the composition of the hexagonal pentlandite is Fe 4.5 Ni 4.5 S8.
[0012] The present invention also provides a method for preparing hexagonal pentlandite, comprising the following steps:
[0013] A) grinding cubic pentlandite to obtain cubic pentlandite powder;
[0014] B) keeping the cubic pentlandite powder at 1-2 GPa and 500-700° C. to synthesize hexagonal pentlandite.
[0015] Preferably, in step A), the particle size of the cubic pentlandite powder is 0.2-2 μm.
[0016] Preferably, in step B), the synthesis of the hexagonal pentlandite is carried out in a multi-faceted anvil.
[0017] Preferably, in step B), the time of heat preservation and pressure preservation is 4 to 8 hours.
[0018] The present invention also provides a use of the above-mentioned pentlandite or the above-mentioned pentlandite prepared by the preparation method as a hydrogen evolution catalyst.
[0019] The present invention also provides a method for electrocatalytic hydrogen evolution, comprising the following steps:
[0020] a) loading a hydrogen evolution catalyst on a carbon cloth to prepare a working electrode;
[0021] The hydrogen evolution catalyst is the pentlandite described above or the pentlandite prepared by the preparation method described above;
[0022] b) using the working electrode, reference electrode and counter electrode to perform electrocatalytic hydrogen evolution in an electrolyte solution.
[0023] The present invention provides a hexagonal pentlandite, wherein the space group of the hexagonal pentlandite is P63 / mmc; the unit cell parameters include: α=90°, β=90°, γ=120°; The hexagonal pentlandite provided by the present invention can be used as a hydrogen evolution catalyst and has excellent hydrogen evolution performance.
[0024] The present invention also provides a method for preparing the above-mentioned hexagonal pentlandite, comprising the following steps: A) grinding cubic pentlandite to obtain cubic pentlandite powder; B) keeping the cubic pentlandite powder at 1 to 2 GPa and 500 to 700°C to synthesize hexagonal pentlandite. The hexagonal pentlandite prepared by the present invention can be used as a hydrogen evolution catalyst with good hydrogen evolution performance. As a hydrogen evolution catalyst, the hexagonal pentlandite has a particle size of 0.2 to 2 μm and a hydrogen evolution performance of 10 mA cm -2 The overpotential is not less than 60mV at high current density (≤205.8mA cm -2 ) for 50 hours without any activity loss, the hydrogen evolution performance is much higher than that of cubic pentlandite, and the hydrogen evolution performance is significantly higher than that of known nano-sulfide hydrogen evolution catalysts. The present invention provides a new high-efficiency catalyst for electrochemical hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a crystal structure diagram of cubic pentlandite in Example 1 of the present invention;
[0026] Figure 2 This is the crystal structure diagram of the ideal hexagonal pentlandite;
[0027] Figure 3 This is an electron paramagnetic resonance test diagram of cubic pentlandite and hexagonal pentlandite in Example 1 of the present invention;
[0028] Figure 4 is a SEM image of hexagonal pentlandite powder;
[0029] Figure 5 is the linear sweep voltammetry curve of the catalyst in the acid solution test;
[0030] Figure 6 is the electrochemical impedance spectroscopy of pentlandite powder;
[0031] Figure 7 This is a persistence test diagram of hexagonal pentlandite powder at a constant potential of 300mV. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention provides a hexagonal pentlandite, wherein the space group of the hexagonal pentlandite is P63 / mmc;
[0034] The unit cell parameters include: α = 90°, β = 90°, γ = 120°;
[0035] In certain embodiments of the present invention, the phase boundaries of the hexagonal pentlandite and cubic pentlandite are 1 GPa / 550°C, 2.1 GPa / 450°C, 4 GPa / 258°C and 6.2 GPa / 200°C, respectively;
[0036] The phase boundary curve conforms to formula (1);
[0037] T=660e -2.203P (1);
[0038] In formula (1), e is a natural constant, the unit of T is °C, and the unit of P is GPa.
[0039] In certain embodiments of the present invention, sulfur vacancies exist in the crystal structure of the hexagonal pentlandite, and one sulfur vacancy exists in 4 to 5 unit cells; specifically, one sulfur vacancy exists in 4.5 unit cells.
[0040] In certain embodiments of the present invention, in the hexagonal pentlandite, the ratio of the number of metal atoms to the number of sulfur atoms is 9:8.
[0041] In certain embodiments of the present invention, the composition of the hexagonal pentlandite is Fe 4.5 Ni 4.5 S8.
[0042] The present invention also provides a method for preparing the above-mentioned hexagonal pentlandite, comprising the following steps:
[0043] A) grinding cubic pentlandite to obtain cubic pentlandite powder;
[0044] B) keeping the cubic pentlandite powder at 1-2 GPa and 500-700° C. to synthesize hexagonal pentlandite.
[0045] In step A):
[0046] In certain embodiments of the present invention, the cubic pentlandite is the most common cubic pentlandite in nickel mining areas, specifically the cubic pentlandite collected from the Xiarihamu nickel mining area in Qinghai.
[0047] The cubic pentlandite is ground to obtain cubic pentlandite powder.
[0048] In certain embodiments of the present invention, the particle size of the cubic pentlandite powder is 0.2-2 μm.
[0049] In step B):
[0050] The cubic pentlandite powder is kept at a temperature of 1 to 2 GPa and a pressure of 500 to 700° C. to synthesize hexagonal pentlandite.
[0051] In some embodiments of the present invention, the temperature of the thermal insulation and pressure maintenance is 700° C., and the pressure is 1 GPa; or the temperature of the thermal insulation and pressure maintenance is 500° C., and the pressure is 2 GPa.
[0052] In certain embodiments of the present invention, the synthesis of pentlandite is carried out in a multi-faceted top anvil.
[0053] In certain embodiments of the present invention, the time of heat preservation and pressure preservation is 4 to 8 hours, specifically 6 hours.
[0054] The present invention also provides a use of the above-mentioned pentlandite or the above-mentioned pentlandite prepared by the preparation method as a hydrogen evolution catalyst.
[0055] In certain embodiments of the present invention, the hexagonal pentlandite is ground into 0.2-2 μm and then applied to electrocatalytic hydrogen evolution.
[0056] The present invention also provides a method for electrocatalytic hydrogen evolution, comprising the following steps:
[0057] a) loading a hydrogen evolution catalyst on a carbon cloth to prepare a working electrode;
[0058] The hydrogen evolution catalyst is the pentlandite described above or the pentlandite prepared by the preparation method described above;
[0059] b) using the working electrode, reference electrode and counter electrode to perform electrocatalytic hydrogen evolution in an electrolyte solution.
[0060] In certain embodiments of the present invention, step a) comprises:
[0061] a-1) mixing a solvent with hydrogen evolution catalyst powder to obtain a catalyst solution;
[0062] The hydrogen evolution catalyst is the pentlandite described above or the pentlandite prepared by the preparation method described above;
[0063] a-2) mixing the catalyst solution with ink to obtain a catalyst ink solution;
[0064] a-3) dropping the catalyst ink solution onto carbon cloth to obtain a catalyst material supported on the carbon cloth, which is a working electrode.
[0065] In step a-1):
[0066] In certain embodiments of the present invention, the solvent includes water and ethanol in a volume ratio of 3:1.
[0067] The hydrogen evolution catalyst powder is obtained by grinding the hydrogen evolution catalyst to obtain a powder with a particle size of 0.2 to 2 μm.
[0068] The concentration of the catalyst solution is 1-3 mg / mL, specifically 2 mg / mL.
[0069] In step a-2):
[0070] In some embodiments of the present invention, the volume ratio of the catalyst solution to the ink is 3:1.
[0071] In step a-3):
[0072] In certain embodiments of the present invention, the amount of the catalyst ink solution is 4 μL; the size of the carbon cloth is 0.5×1 cm.
[0073] In step b):
[0074] In some embodiments of the present invention, the reference electrode is Ag / AgCl, and the counter electrode is a graphite rod.
[0075] In certain embodiments of the present invention, the electrolyte solution is an acidic solution with a concentration of 0.4-0.6 mol / L; specifically, a 0.5 mol / L H2SO4 solution.
[0076] In certain embodiments of the present invention, the current density for electrocatalytic hydrogen evolution is 10 mA cm -2 .
[0077] As a hydrogen evolution catalyst, hexagonal pentlandite with a particle size of 0.2 to 2 μm can react with water at 10 mA cm -2 The overpotential is not less than 60mV at high current density (≤205.8mA cm -2 ) for 50 h without any loss of activity.
[0078] In order to further illustrate the present invention, a hexagonal pentlandite, a preparation method thereof and electrocatalytic hydrogen evolution provided by the present invention are described in detail below in conjunction with examples, but it should not be construed as limiting the scope of protection of the present invention.
[0079] The raw materials used in the examples are generally commercially available.
[0080] The cubic pentlandite in the embodiment is cubic pentlandite collected from the Xiarihamu nickel mining area in Qinghai.
[0081] Example 1
[0082] A method for preparing hexagonal pentlandite comprises the following steps:
[0083] 1) Grinding cubic pentlandite (cPn1) with an agate mortar to obtain cubic pentlandite powder with a particle size of 0.2 to 2 μm;
[0084] 2) The cubic pentlandite powder is kept at 700° C. and 1 GPa for 6 hours in a multi-faceted top anvil to synthesize hexagonal pentlandite (hPn1).
[0085] Example 2
[0086] 1) Grinding cubic pentlandite (cPn2) with an agate mortar to obtain cubic pentlandite powder with a particle size of 0.2 to 2 μm;
[0087] 2) The cubic pentlandite powder is kept at 500° C. and 2 GPa for 6 hours in a multi-faceted top anvil to synthesize hexagonal pentlandite (hPn2).
[0088] The compositions of cubic pentlandite and hexagonal pentlandite in Examples 1-2 are shown in Table 1.
[0089] Table 1 Composition of cubic pentlandite and hexagonal pentlandite in Examples 1 to 2 (wt%)
[0090]
[0091] Figure 1 The crystal structure diagram of cubic pentlandite in Example 1 of the present invention is shown in FIG. The yellow spheres are Ni and Fe atoms, Ni and Fe have the same crystal occupancy, and the yellow spheres are S atoms.
[0092] The single crystal Debye diffraction of the hexagonal pentlandite in Example 1 was performed using a single crystal diffractometer to obtain the ideal crystal structure and unit cell parameters of the hexagonal pentlandite. Figure 2 The figure is a crystal structure diagram of an ideal hexagonal pentlandite. Yellow represents sulfur atoms, turquoise represents metal atoms, and the metal atoms Fe and Ni are in the same position in the crystal structure. The space group of the hexagonal pentlandite is P63 / mmc, and the unit cell parameters include: α=90°, β=90°, γ=120°; At the same time, from Figure 2 It can be seen that in the ideal crystal structure of hexagonal pentlandite, the ratio of metal atoms to sulfur atoms is 1:1, that is, FeNiS2, which is slightly different from the ratio of metal atoms to sulfur atoms of cubic pentlandite, which is 9:8.
[0093] The sulfur vacancies of cubic pentlandite and hexagonal pentlandite in Example 1 were tested by electron paramagnetic resonance. Figure 3 shown. Figure 3 This is the electron paramagnetic resonance test diagram of cubic pentlandite and hexagonal pentlandite in Example 1 of the present invention, where cPn is cubic pentlandite and hPn is hexagonal pentlandite. The higher the peak, the more sulfur vacancies there are. Figure 3 It can be seen that hexagonal pentlandite has more sulfur vacancies than cubic pentlandite.
[0094] Cubic pentlandite is thought to contain 0.275 sulfur vacancies per unit cell, and hexagonal pentlandite has higher sulfur vacancies than this. Figure 2 In the ideal crystal structure of hexagonal pentlandite, the ratio of metal atoms to sulfur atoms is 1:1, that is, FeNiS2, which is slightly different from the ratio of metal atoms to sulfur atoms of cubic pentlandite, which is 9:8. However, after the phase transformation from cubic pentlandite to hexagonal pentlandite, the element content does not change, that is, the actual ratio of metal atoms to sulfur atoms in hexagonal pentlandite should be the same as that of cubic pentlandite, which is still 9:8. A more reasonable explanation may be that for hexagonal pentlandite, there is a sulfur vacancy in 4.5 unit cells, so its molecular formula can be made up of Fe 4.5 Ni 4.5 S8. That is, in the crystal structure of the hexagonal pentlandite of the present invention, there is one sulfur vacancy in 4.5 unit cells.
[0095] The hexagonal pentlandite obtained in Example 1 was manually ground into a powder of 0.2 to 2 μm to obtain hexagonal pentlandite powder. The hexagonal pentlandite powder was subjected to scanning electron microscopy analysis. Figure 4 shown. Figure 4 This is the SEM image of hexagonal pentlandite powder.
[0096] The electrochemical test of the hexagonal pentlandite powder showed that the composition of the hexagonal pentlandite was Fe 4.5 Ni 4.5 S8. Grind cubic pentlandite of the same composition manually into a powder of 0.2-2 μm to obtain cubic pentlandite powder, and perform an electrochemical hydrogen evolution test on the cubic pentlandite powder and the hexagonal pentlandite powder to compare their hydrogen evolution performances.
[0097] Specifically, the electrochemical properties of the catalyst were measured by a standard three-electrode device using a CHI760e potentiostat: the catalyst material loaded on the carbon cloth (the preparation method includes: mixing water and ethanol in a volume ratio of 3:1 to obtain a solvent, mixing the solvent with a hydrogen evolution catalyst powder (the hydrogen evolution catalyst powder is cubic pentlandite powder or hexagonal pentlandite powder) to obtain a catalyst solution with a concentration of 2 mg / mL, mixing the catalyst solution with ink in a volume ratio of 3:1 to obtain a catalyst ink solution, taking 4 μL of the ink solution and dropping it on a carbon cloth with a size of 0.5×1 cm to obtain a catalyst material loaded on the carbon cloth; Ag / AgCl and a graphite rod were used as working electrodes, reference electrodes, and counter electrodes, respectively. An acidic 0.5 mol / L H2SO4 solution was used for electrochemical testing. A linear sweep voltammetry method with a scan rate of 10 mV / s was used. The recording range of the electrochemical impedance spectrum was 0.01 to 100000 Hz. All measurements were performed at room temperature.
[0098] Figure 5 The linear sweep voltammetry curve of the catalyst in the acid solution test. Where cPn is cubic pentlandite powder and hPn is hexagonal pentlandite powder. Figure 5 It can be seen that cPn is 10mA / cm 2 The overpotential is 168mV at a current density of 10mA / cm 2 It exhibits an overpotential of 60 mV at a current density of , and the hydrogen evolution performance is significantly improved.
[0099] The hydrogen evolution overpotential of the non-nano hexagonal pyrite in the present invention is compared with the hydrogen evolution overpotential of other high-performance nano sulfide catalysts. The results are shown in Table 2.
[0100] Table 2 Comparison of hydrogen evolution overpotential of hexagonal pentlandite and other high performance nanosulfide catalysts
[0101]
[0102] As can be seen from Table 2, the hexagonal pentlandite provided by the present invention has a 2 At a current density of , the overpotential does not exceed 60mV, and the hydrogen evolution performance is significantly better.
[0103] In an acidic 0.5 mol / L H2SO4 solution, at 300 mV, the electrochemical impedance spectroscopy (EIS) of the cubic pentlandite powder and the hexagonal pentlandite powder was studied as follows: Figure 6 shown. Figure 6 is the electrochemical impedance spectrum of pentlandite powder, where cPn is cubic pentlandite powder and hPn is hexagonal pentlandite powder. Figure 6It can be seen that the charge transfer resistance (Rct) of hPn is 204.7Ω, which is significantly lower than that of cPn (408.7Ω).
[0104] The present invention conducts a persistence test on the hexagonal pentlandite powder at a constant potential of 300mV, and the results are as follows: Figure 7 shown. Figure 7 This is a graph showing the endurance test of hexagonal pentlandite powder at a constant potential of 300mV. Figure 7 It can be seen that hPn is at 300mV and high current density (≤205.8mA cm -2 ) under 50h without any activity loss.
[0105] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A hexagonal pentlandite, characterized in that: The space group of the hexagonal pentlandite is P63 / mmc; The unit cell parameters include: α = 90°, β = 90°, γ = 120°, The preparation method of the hexagonal pentlandite comprises the following steps: A) grinding cubic pentlandite to obtain cubic pentlandite powder; B) keeping the cubic pentlandite powder at 1 to 2 GPa and 500 to 700° C. to synthesize hexagonal pentlandite; In step A), the particle size of the cubic pentlandite powder is 0.2-2 μm.
2. The hexagonal pyrite according to claim 1, characterized in that The phase boundaries of the hexagonal pentlandite and the cubic pentlandite are 1 GPa / 550°C, 2.1 GPa / 450°C, 4 GPa / 258°C and 6.2 GPa / 200°C respectively; The phase boundary curve conforms to formula (1); T=660e -2.203P (1); In formula (1), e is a natural constant, the unit of T is °C, and the unit of P is GPa.
3. The hexagonal pyrite according to claim 1, characterized in that In the hexagonal pentlandite, the ratio of the number of metal atoms to the number of sulfur atoms is 9:
8.
4. The hexagonal pyrite according to claim 1, characterized in that The composition of the hexagonal pentlandite is Fe 4.5 Ni 4.5 S8.
5. The hexagonal pyrite according to claim 1, characterized in that In step B), the synthesis of the hexagonal pentlandite is carried out in a multi-faceted anvil.
6. The hexagonal pyrite according to claim 1, characterized in that In step B), the time of heat preservation and pressure preservation is 4 to 8 hours.
7. Use of the pentlandite obtained from the pentlandite according to any one of claims 1 to 6 as a hydrogen evolution catalyst.
8. A method for electrocatalytic hydrogen evolution, comprising the following steps: a) loading a hydrogen evolution catalyst on a carbon cloth to prepare a working electrode; The hydrogen evolution catalyst is pentlandite prepared from the pentlandite according to any one of claims 1 to 6; b) using the working electrode, reference electrode and counter electrode to perform electrocatalytic hydrogen evolution in an electrolyte solution.
Citation Information
Patent Citations
Electrocatalyst for hydrogen evolution and preparation method and application thereof
CN110624567A